Remarks on Receiving the 2003 AAPHD President’s Award - Stanley Lotzkar, DDS, MPH
Thank you very much, Dr. Maas. I feel very honored and grateful to be this year’s recipient of the President’s Award. The relationship between the board and AAPHD has always been a very close one, even in the time before 1975, when AAPHD shared sponsorship responsibilities with the Dental Section of the American Public Health Association. The end of dual sponsorship led to a lasting era of cooperation and mutual support that in turn has benefited both organizations